Emotional regulation self-efficacy and impulsivity effects on college students' risk-taking behavior: a cross-sectional study - Zhang, Ruoyu; Zhang, Chen; Huang, Liying (Frontiers in Psychology, 2025)
BackgroundThe adventurous behaviors of college students are becoming increasingly diverse. This study is grounded in the dual-process theory model of impulsivity. To explore the impact of the match between impulsivity and emotional regulation self-efficacy on college student multi-domain risk-taking behavior and examine whether impulsivity played a mediating role, using a polynomial regression and response surface analysis.MethodsA questionnaire survey was conducted with 638 college students from online and offline, to investigate their impulsivity, emotional self-efficacy, multi-domain risk-taking behavior.Results(1) Impulsivity is significantly positively correlated with risk-taking behavior across various domains. Emotional self-efficacy is significantly negatively correlated with impulsivity, as well as with risk-taking behaviors in the health/safety and moral domains. (2) College students with high impulsivity and high emotional regulation self-efficacy engage in more health/safety, moral, and recreational risk-taking behaviors than those with low impulsivity and low emotional regulation self-efficacy. (3) College students with high impulsivity and low emotional regulation self-efficacy exhibit a greater number of health/safety, moral, and recreational risk-taking behaviors than those with low impulsivity and high emotional regulation self-efficacy. (4) In the male population, impulsivity plays a full mediating role between emotional regulation self-efficacy and various domains of risk-taking behavior. In the female population, impulsivity serves as a full mediator only in the domains of health/safety, moral, and economic risk-taking behaviors, while it acts as a partial mediator in the domains of recreational and social risk-taking behaviors.ConclusionThe present study reveals the mechanisms through which different combinations of high and low impulsivity and emotional self-efficacy influence multi-domain risk-taking behaviors among college students and validated the mediating role of impulsivity. This study validates the dual-process theory of impulsivity and provides research experience for future interventions targeting risk-taking behaviors across various domains among college students of different genders.